Perancangan Interior Study Lounge Café di Surabaya - Vaniasari Hugeng; Hedy Constancia Indrani (Intra, 2016)
Study Lounge Café is a facility which is designed to meet the individual needs of high school and university students, such as learning or doing their assignments. This study lounge café is equipped with facilities such as air conditioning, wifi, photocopier, printer, scanner, computer, and other supporting facilities to increase the effectiveness of the work. The concept used is “A Fun Place to Study”, which is applied to “Playground” theme. Both concept and the theme were chosen to create a comfortable learning activities through interesting yet fun ambience. The concept also can be seen from the use of bright colors, playground-equipment-formed furniture, and the addition of quotes that motivates visitors. The design uses design thinking method according to Kembel.